Cutaneous Mycoses among Rice Farmers in Anambra State, Nigeria. (25th September 2013) - Ekwealor, Chito Clare; Oyeka, Christie Amechi
Abstract : Rice grain is one of the world's most important food crops, and its cultivation is a major occupation in Anambra State, Nigeria. These rice farmers are exposed to various agents that predispose them to cutaneous mycoses. The aim of this work was to screen rice farmers for lesions suggestive of cutaneous mycoses and to isolate and identify fungal agents associated with the infection. This survey was carried out between November 2009 and June 2011 in Anambra State, Nigeria. Clinical samples collected from 201 farmers with lesions suggestive of cutaneous mycoses were processed and the organisms identified. Questionnaires were used to obtain other necessary data and were statistically analyzed. Of the 2, 580 rice farmers screened, 201 (7.79%) showed positive lesions. Organisms recovered included Microsporum audouinii, Microsporum ferrugineum, Trichophyton megnini, Trichophyton tonsurans, Trichophyton rubrum, Aspergillus terrus, Aspergillus candidus, Aspergillus scleriotorum, Aspergillus niger, Aspergillus flavus, Scopulariopsis sp., Chrysosporium sp., Eupenicillium javanicum, Fusarium sp., Penicillium aculeatum, and Penicillium pinophilum . At the end of this work, onychomycosis was observed to be the most prevalent with nondermatophyte molds now becoming very important agents of cutaneous mycoses among rice farmer.